Derechos humanos y la dignidad humana como presupuesto de la eutanasia - Aguilera Portales, Rafael (2012)
Human rights and human dignity as assumption of euthanasia This article has a philosophical approach to provide us interesting thoughts in order to understand the euthanasia. To that end, initially it analyzes death connotations in the society in which we live followed by a broad reflection around death’s problem and human dignity in the capitalist society. Next, a rigorous analysis on human’s dignity idea in order to link its content with euthanasia reflection as well as with the end of life care is presented; reaching to critical conclusions of existing medical and legal regulations. Finally, some allegations and suggestions of analyzed issues are submitted.